Analysis of constraints in dairy farming in Kerala multistakeholder perspective - S, Smitha; Devi, MCA; G, Letha Devi; S, Subash (Indian Journal of Dairy Science, 2019)
The study was undertaken in Kerala to evaluate the challenges of dairy farming at research, extension and farmers’ level. The total number of the 200 respondent farmers and stakeholders from research and extension domain in the study area were selected randomly. Garret’s ranking technique was adopted to analyze the constraints faced by the stakeholders in the study area. The major constraint faced by the dairy farmers were the high cost of cattle feed and high cost of veterinary service and medicine was the second major constraint felt by the farmers. The major constraint faced by the officials involved in extension services were large number of schemes for implementation in Panchayat and block level followed by lack of transportation facilities to make field visit. In research system, the major constraint was the teaching and extension mandates of universities followed by time constraint for technology transfer.